2019
DOI: 10.1002/prca.201900103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Malonylation, Succinylation, and Glutarylation in Serum Proteins of Acute Myocardial Infarction Patients

Abstract: Purpose To identify protein malonylation, succinylation, and glutarylation in human and rat serum. Experimental design Immunoprecipitation coupled with MS/MS is employed to compare the relative abundance of malonylation, succinylation, and glutarylation of serum protein in acute myocardial infarction human and rat. Results One hundred thirty and 48 unique malonylated, succinylated, or glutarylated peptides are found in human and rat serum, respectively. Succinylation is the most predominant modification. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
(29 reference statements)
2
23
0
Order By: Relevance
“…By contrast, inhibition of MCD leads to increasing myocardial levels of malonyl-CoA, an intracellular inhibitor of mitochondrial FA uptake, to decrease FA oxidation and enhance glucose oxidation, which ultimately causes the decrease in toxic byproducts (lactate and protons) to augment cardiac function and cardiac efficiency and prevents myocardial ischemic injury [109][110][111]. Also, a recent study reveals the malonylation of serum proteins in acute MI humans and rats [112]. Therefore, MCD is an essential regulator of protein malonylation and CVDs.…”
Section: Malonate and Malonylationmentioning
confidence: 99%
“…By contrast, inhibition of MCD leads to increasing myocardial levels of malonyl-CoA, an intracellular inhibitor of mitochondrial FA uptake, to decrease FA oxidation and enhance glucose oxidation, which ultimately causes the decrease in toxic byproducts (lactate and protons) to augment cardiac function and cardiac efficiency and prevents myocardial ischemic injury [109][110][111]. Also, a recent study reveals the malonylation of serum proteins in acute MI humans and rats [112]. Therefore, MCD is an essential regulator of protein malonylation and CVDs.…”
Section: Malonate and Malonylationmentioning
confidence: 99%
“… Bao et al (2019) revealed that Kglu occurs at 27 lysine residues on human core histones. Zhou et al (2020) reported 4 kinds of glutarylated proteins with 10 sites in human serum. It shows that Kglu occurred in different species, and most of glutarylated proteins contain at least two Kglu sites in Table 1 .…”
Section: Proteomic Profiling Of Lysine Glutarylationmentioning
confidence: 99%
“…Antibodies are crucial for experimental studies, especially for the identification of protein PTMs. Therefore, we have reviewed the experimental studies on antibody for lysine glutarylation, and found eight related articles ( Tan et al, 2014 ; Xie L. et al, 2016 ; Zhou et al, 2016 , 2020 ; Schmiesing et al, 2018 ; Bao et al, 2019 ; Cheng et al, 2019 ; Wang et al, 2020 ). The specific Methods and reagents used in previous studies were summarized in Supplementary Table 1 .…”
Section: Proteomic Profiling Of Lysine Glutarylationmentioning
confidence: 99%
See 1 more Smart Citation
“…glycolysis and the synthesis of bioactive substances. Malonylation has been reported to use malonyl-CoA as a substrate in the reaction [9]. At present, with advances in high-throughput experimental techniques, thousands of peptide segments containing lysine malonylation have been discovered.…”
mentioning
confidence: 99%